Hyperandrogenemia in polycystic ovary syndrome: exploration of the role of free testosterone and androstenedione in metabolic phenotype - Lerchbaum, Elisabeth; Schwetz, Verena; Rabe, Thomas; Giuliani, Albrecht; Obermayer-Pietsch, Barbara (PLOS ONE, 2014)
Objective To evaluate the association between androstenedione, testosterone, and free testosterone and metabolic disturbances in polycystic ovary syndrome. Methods We analyzed the association between androstenedione, testosterone, and free testosterone and metabolic parameters in a cross-sectional study including 706 polycystic ovary syndrome and 140 BMI-matched healthy women. Polycystic ovary syndrome women were categorized into 4 groups: normal androstenedione and normal free testosterone (NA/NFT), elevated androstenedione and normal free testosterone (HA/NFT), normal androstenedione and elevated free testosterone (NA/HFT), elevated androstenedione and free testosterone (HA/HFT). Results Polycystic ovary syndrome women with elevated free testosterone levels (HA/HFT and NA/HFT) have an adverse metabolic profile including 2 h glucose, HbA1c, fasting and 2 h insulin, area under the insulin response curve, insulin resistance, insulin sensitivity index (Matsuda), triglycerides, total and high density lipoprotein cholesterol levels compared to NA/NFT (p<0.05 for all age- and BMI-adjusted analyses). In binary logistic regression analysis adjusted for age and BMI, odds ratio for insulin resistance was 2.78 (1.34-5.75, p = 0.006) for polycystic ovary syndrome women with HA/HFT compared to NA/NFT. We found no significantly increased risk of metabolic disorders in polycystic ovary syndrome women with HA/NFT. In multiple linear regression analyses (age- and BMI-adjusted), we found a significant negative association between androstenedione/free testosterone-ratio and area under the insulin response curve, insulin resistance, and total cholesterol/high density lipoprotein cholesterol-ratio and a positive association with Matsuda-index, and high density lipoprotein cholesterol (p<0.05 for all). Conclusions Polycystic ovary syndrome women with elevated free testosterone levels but not with isolated androstenedione elevation have an adverse metabolic phenotype. Further, a higher androstenedione/free testosterone-ratio was independently associated with a beneficial metabolic profile.
Gesehen am 13.07.2020